Herpes Zoster in a world class triathlete: A case report and evaluation of training schedules in relation to immune status - Lai, L.P.; Shilt, J. S.; Georgy, J. S. (International Journal of Sport & Health Science, 2015)
Herpes Zoster, also known as Shingles, is an eruption of latent Varicella Zoster viral particles which classically leads to a dermatomal skin eruption. While the causes of this reactivation are yet unknown, Shingles usually affects older individuals or those who are immunocompromised due to other disease processes or pharmacotherapy following organ transplant. We report the unique case of a world class triathlete who developed a painful dermatomal rash following a period of particularly intense training, travel, and competition. His training schedule for three months following the illness and return to competition is documented. The athlete's subsequent period of underperformance and profound fatigue suggest an inadequate recovery period. Review of the literature reveals a paucity of information describing an appropriate return to training and competition.